V16. MRI abnormalities of the cerebellar cortex and nuclei in SCA3, SCA6, and Friedreich's ataxia. Issue 8 (August 2015) - Stefanescu, M.R.; Dohnalek, M.; Maderwald, S.; Thürling, M.; Minnerop, M.; Beck, A.; Schlamann, M.; Diedrichsen, J.; Ladd, M.E.; Timmann, D.
<x xml:space="preserve">Abstract</x> In the present study, susceptibility weighted imaging (SWI) was used to show atrophy of cerebellar nuclei in spinocerebellar ataxia type 6 (SCA6), Friedreich ataxia (FRDA), and spinocerebellar ataxia type 3 (SCA3). We tested the hypothesis that cerebellar nuclei are smaller in FRDA and SCA3 compared to healthy controls, but relatively preserved in SCA6. In addition, 7T fMRI was performed with optimized normalization methods to assess function of the cerebellar cortex and nuclei during simple hand movements. Twelve SCA6 patients (age range 41–76 years, five female), twelve FRDA patients (age range 21–55 years, seven female), and ten SCA3 patients (age range 34–67 years, three female), and age- and gender-matched control groups (total n = 23, age range 22–75 years, ten female) were included. As expected, volume of the cerebellum was most markedly reduced in SCA6, with no significant reduction in FRDA and a slight decrease in SCA3. Atrophy of the cerebellar nuclei was not only present in FRDA and SCA3, but also in SCA6. In fact, volume reduction of the nuclei was most marked in SCA6. On a functional level, fMRI signal was altered both within the cerebellar cortex and the nuclei in the three disorders. In the nuclei, the reduction was most prominent in FRDA. Different from initial expectations, the decrease of fMRI signal in the cerebellar cortex appeared more prominent in SCA3 and FRDA than in SCA6. These findings will be discussed in further detail in the light of the known pathohistology of the diseases. The study was supported by the EU Marie Curie Initial Training Network (ITN) grant C7 ("Cerebellar-Cortical Control: Cells, Circuits, Computation, and Clinic").